Innovative Utilization of Upcycled Waste Materials in the Construction of Useful and Attractive Household Articles - Akintayo, W. L.; Idowu, S. A. (Africa Environmental Review Journal, 2022)
The study was carried out to examine the innovative utilization of upcycled waste materials in the construction of useful and attractive household articles. The research design adopted for the study are experimental and survey research. The experimental design dealed with the steps involved in the construction of the articles while the survey design encompasses the assessment of the respondents on the acceptability of the articles produced. Two articles produced using upcycling method are foot-stool and storage box pouf. An open-ended questionnaire was designed by the researcher for assessing the acceptability of the articles produced. The questionnaire was administered on 30 respondents which comprised of academic staff, non-academic staff and students within the Tai Solarin University of Education which was the study area. Data collected were analysed using frequency counts, percentages, mean and standard deviation while the quality assessment of the two articles produced was based on colour, appearance, and cost. Among the major findings are that majority of the respondents adjudged both the footstool pouf and storage box produced of been of high quality in terms of Colour (56.7%, 53.3%), appearance (50%, 60.0%) and cost (60%, 60.0%%) respectively; the produced footstool and storage box are confirmed to be durable and affordable; the use of upcycled waste materials were adjudged to go a long way to encourage the patronage of locally made fabric materials and would also create new market opportunities for traditional textile designers. The study’s findings led to the following suggestions. Upcycling information should be more specific on what, when, and where to recycle; To maximise material use, clothing and textiles should be upcycled at several levels; Government and other stake holders should focus on waste management in textiles using upcycling techniques much equal to inventing new products and technologies.